Peer reflective groups: Creating a nurturing and safe community for aspiring clinical psychologists to build their collective voice. (January 2023) - Taylor, Charlotte; Daniilidi, Xeni; Tan, Sarah; Huckridge, Jaymie
Assistant Psychologist (AP) and Honorary Assistant Psychologist (HAP) roles provide an opportunity to gain the experience needed to progress onto the Clinical Psychology doctorate, making them very competitive to obtain. Nationally, there have been reports that people fulfilling these roles can face a number of challenges including poorly defined job descriptions, difficulty developing a voice within hierarchical organisation structures and balancing competing demands on time. This paper tells the story of a peer reflective group set up for APs and HAPs in the paediatric health psychology team, to provide a supportive space for aspiring psychologists to meet together. The evolution of the group and its impact are discussed, and recommendations for setting up similar groups in other services are made.